Macroeconomic Aggregates and Investment Fluctuations: the Example of WAEMU Countries - Ndiaye, Cheikh Tidiane (DEMO, 2017)
Th is article provides an assessment of the impact of changes in macroeconomic aggregates on the investment of the WAEMU countries. Th e study is based on structural modeling of unobserved components likely to highlight the links between investment and macroeconomic variables. The results suggest the recurrence of negative impacts on investment. Macroeconomic aggregates (GDP, inflation, savings) exert a pro-cyclical behavior on the investment. On the other hand, fiscal balance is countercyclical following the different phases of investment cycle. Business investment should be a priority of national fiscal policies in the member countries of the Union for sustainable economic development.(original abstract)
Keywords: Macroeconomics; Macroeconomic policy; Investment cycles; Investment